2019
DOI: 10.1111/cod.13363
|View full text |Cite
|
Sign up to set email alerts
|

Allergic contact dermatitis in atopic individuals: Results of a 30‐year retrospective study

Abstract: Background: The association between atopic dermatitis (AD) and contact allergy, remains unclear, with studies to date showing conflicting results.Objectives: To investigate the prevalence of contact allergy in AD individuals compared to those without AD.Methods: Results of 46 250 patients patch tested in a single centre over a span of 30 years were reviewed, comparing those with AD with those without AD. Collected data were analysed with corrections for multiple confounding variables, including date of patch t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 40 publications
1
28
1
3
Order By: Relevance
“…Several studies including hairdressers have also shown a significant and early high risk of developing ACD during the first years of starting their jobs 14‐17 . Moreover, although the association between contact allergy and atopic dermatitis remains controversial in the literature, 18‐21 34.7% of our patients reported a positive personal history of atopic disease.…”
Section: Discussionmentioning
confidence: 72%
“…Several studies including hairdressers have also shown a significant and early high risk of developing ACD during the first years of starting their jobs 14‐17 . Moreover, although the association between contact allergy and atopic dermatitis remains controversial in the literature, 18‐21 34.7% of our patients reported a positive personal history of atopic disease.…”
Section: Discussionmentioning
confidence: 72%
“…The disruption of the skin barrier in AD patients raises the possibility of both sensitization and irritation, which could explain the increased prevalence of contact dermatitis that finally exert a detrimental effect also to AD (Teo, McFadden, White, Lynch, & Banerjee, ). The diagnosis of contact dermatitis in all patients but especially in AD patients should be conducted following the recently available Italian Guidelines in Patch Testing—adapted from the European Society of Contact Dermatitis (Stingeni et al, ).…”
Section: General Measures and Avoidance Strategiesmentioning
confidence: 99%
“…It is noteworthy that this sensitization pathway for sesquiterpene lactones, which are detected in the conventional patch test and possibly mediated via inhalation of airborne pollen or mucosal contact of airborne plant trichomes, 65 has already been discussed for some time. 66,67 However, results of no correlation between a positive aeroallergen patch test outcome and a respiratory allergy have also been , 'AEA' air-exposed skin areas (face, neck, forearms, hands) involved, 'AR' allergic rhinitis (past or present), 'E2D' patch test exposure time of 2 days, 'LFC' use of large Finn Chambers â , 'POLY' polysensitization to three or more independent allergens (haptens) of the DKG baseline series, 'SLS' irritant patch test reaction to sodium lauryl sulphate 0.25% aqueous. AD, atopic dermatitis; CI, confidence interval.…”
Section: Discussionmentioning
confidence: 99%
“…Hypothetically, as recently suggested for FLG loss‐of‐function mutations, a pathway that unites the airways and the skin could be responsible for primary respiratory sensitization to aeroallergens being demonstrated by patch testing. It is noteworthy that this sensitization pathway for sesquiterpene lactones, which are detected in the conventional patch test and possibly mediated via inhalation of airborne pollen or mucosal contact of airborne plant trichomes, has already been discussed for some time . However, results of no correlation between a positive aeroallergen patch test outcome and a respiratory allergy have also been reported .…”
Section: Discussionmentioning
confidence: 99%